Respostas da vegetação remanescente e da regeneração natural em floresta ombrófila mista cinco anos após intervenções de manejo - Hack, Cristiano (2007)
This research work was accomplished at a Mixed Rainy Forest in advanced stage of natural regeneration and that had as objectives: to describe the original vegetation of the place about to the floristic and structure; to compare the original vegetation, after-cut and current submitted to different intensities of intervention; to quantify the mortality of the remaining trees passed five years of the intervention; to evaluate the ingression of new individuals in the adult vegetation, as well as the growth of the remaining species; to characterize the natural regeneration of the palce and to compare the variable analyzed between the different treatments. The works had been carried through in Fazenda Tupi, property of Grupo VIPAL S/A, in the city of Nova Prata - RS. The treatments consisted in interventions of management of different intensities in the forest, five years before the current measurement, interventions which had accomplished and detailed by Borsoi (2004). The results gotten in the current inventory (in such a way of the adult vegetation as of natural regeneration) had been compared with the results of the inventory of the original vegetation and the remaining vegetation soon after the application of the treatments. The biggest alterations after-cut in the structure of the forest, mainly the reduction of the density and the basal area and volume of the vegetation had occurred in palces where the interventions had been more intense. Five years after the interventions the forest shows signals of that it is if organizing, however not yet reached the level of the original vegetation, as much in density how much in volume. The floristic diversity was bigger in the current vegetation of what in the original. The hardly opening of the canopy made possible a bigger number of ingression of individuals and species in the adult vegetation. The natural regeneration of the current vegetation was presented much more dense than the original vegetation. For a better understanding of the dynamics of the vegetation and the factors that influence in the development and recovery of it after the human interventions, continuous measuring of this area are demanded to it, relating the results with ambient factors and of ground.